Investigation of anode-supported SOFC with cobalt-containing cathode and GDC interlayer - Jung, Hun-Gi; Sun, Yang-Kook; Jung, Hwa Young; Park, Jong Sung; Kim, Hae-Ryoung; Kim, Gyeung-Ho; Lee, Hae-Weon; Lee, Jong-Ho (ELSEVIER SCIENCE BV, 2008)
The YSZ-based anode-supported solid oxide fuel cells were fabricated with Co-containing cathode such as La0.6Sr0.4Co0.2Fe0.8O3 (LSCF), La0.6Sr0.4CoO3 (LSCo) and Sm0.5Sr0.5CoO3 (SSCo). To prevent the interfacial reaction between Co-containing cathodes and YSZ electrolyte, Gd0.1Ce0.9O2 (GDC) interlayer was introduced. According to the analysis of the electrochemical performance, the LSM cathode cell had the maximum power density of around 0.56 W/cm(2) at 700 degrees C whereas the SSCo cathode cell achieved the highest maximum power density of around 1.26 W/cm(2). Furthermore, all the Co-containing cathode cells had the smaller polarization resistance than the LSM cathode cell. However, resistive reaction product (such as SrZrO3) between LSCF and YSZ induced the largest ohmic ASR of the unit cell with LSCF cathode, resulted in much lower cell performance than other Co-containing cathode cells. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: OXIDE FUEL-CELLS; PERFORMANCE; PEROVSKITES; PR; LA; SM; LN; ND